Comparison of rebound tonometry and non-contact airpuff tonometry to Goldmann applanation tonometry - Demirci, Goktug (Ther Adv Ophthalmol, 2019)
PURPOSE: The aim of this study was to compare the intraocular pressure measurements obtained from healthy subjects with the rebound tonometry, non-contact airpuff tonometry, and Goldmann applanation tonometry in different age groups. METHODS: A total of 180 eyes of 90 healthy subjects were included in the study. According to the subjects’ ages, the eyes were categorized into three groups: group 1 (age: 7–17 years), group 2 (age: 18–40 years), and group 3 (age: 41–75 years). Intraocular pressure was measured on each subject always in the same order: rebound tonometry, non-contact airpuff tonometry, and Goldmann applanation tonometry. Central corneal thickness values were obtained using ultrasonic pachymetry. One-way repeated-measures analysis of variance, Pearson’s correlation coefficient, and Bland–Altman analysis were used for the statistical assessment. RESULTS: The mean corneal thickness was found to be 604 ± 13 µm, 546 ± 15 µm, and 547 ± 15 µm in group 1, group 2, and group 3, respectively. Non-contact airpuff tonometry was significantly higher than both Goldmann applanation tonometry and rebound tonometry measurements in all groups (p < 0.001, for all). No statistical difference between Goldmann applanation tonometry and rebound tonometry measurements was found in group 1 (p = 0.248), group 2 (p = 0.63), and group 3 (p = 0.126). There was a significant positive correlation in the meaning of intraocular pressure measurements between rebound tonometry and non-contact airpuff tonometry; non-contact airpuff tonometry and Goldmann applanation tonometry; and Goldmann applanation tonometry and rebound tonometry in all groups. CONCLUSION: As a result, without need for topical anesthesia, fast measurement and ease-of-use rebound tonometry is a reliable alternative to Goldmann applanation tonometry in different age groups.